A perylene diimide electron acceptor with a triptycene core for organic solar cells. Issue 12 (14th March 2017) - Liu, Xiaofeng; Cai, Yunhao; Huang, Xuebin; Zhang, Rubo; Sun, Xiaobo
Abstract : A novel nonplanar 3D acceptor material for organic solar cells composed of three perylene diimide units and a triptycene core is synthesized and characterized. Abstract : A new 3D-structured acceptorTP3, in which three perylene diimide (PDI) units are connected together by a triptycene (TPC) core, is synthesized and characterized. Organic solar cells (OSCs) fabricated with a PTB7-Th:TP3 blend film as the active layer have been investigated and the best power conversion efficiency (PCE) of 3.16% is achieved by adding 0.5% DIO. Our studies suggest that the introduction of the TPC core could suppress the strong self-aggregation tendency of the PDI chromophores.